Hydrothermally etched titanium: a review on a promising mechano-bactericidal surface for implant applications. (December 2021) - Hayles, A.; Hasan, J.; Bright, R.; Palms, D.; Brown, T.; Barker, D.; Vasilev, K.
Abstract: The growing demand for titanium-based implants and the subsequent rise in implant-associated infections necessitate novel developments in anti-infective technologies. Recent research has drawn inspiration from nature to solve this problem. The nanoscale topography observed on cicada and dragonfly wings serves as a blueprint for synthetic analogs which seek to kill bacteria on contact through mechanical forces. This type of interaction has been dubbed the mechano-bactericidal effect. Various techniques have been utilized to mimic and improve upon these natural bactericidal surfaces. Alkaline hydrothermal etching is a simple and cost-effective technique to fabricate nanoscale protrusions on titanium and its alloys. This review aims to consolidate the current knowledge surrounding how fabrication parameters lead to varying surface topographies on titanium substrates, and subsequently, how surface topography and bacterial characteristics affect bactericidal activity. The bactericidal mechanism of hydrothermally etched titanium is inferred from comparisons with similar mechano-bactericidal biomaterials. The hostility of hydrothermally etched titanium toward bacteria is discussed in contrast to the observed host cell compatibility. Last, suggestions are made for the standardization of terminology in this emerging field. Graphical abstract: Image 1 Highlights: Mechano-bactericidal titanium can be easily and cheaply fabricated by hydrothermal etching. Surface topographical features can be tuned based on defined fabrication parameters. The bactericidal mechanism is due to mechanical interaction and downstream metabolic effects. Efficacy is determined by surface morphology and biological characteristics of bacteria. Hydrothermally etched titanium is permissive to host tissue and suitable for implantation.